Efficacy and safety of avapritinib in previously treated patients with advanced systemic mastocytosis - Reiter, Andreas; Schwaab, Juliana; DeAngelo, Daniel J.; Gotlib, Jason; Deininger, Michael W.; Pettit, Kristen M.; Alvarez-Twose, Iván; Vannucchi, Alessandro M.; Panse, Jens; Platzbecker, Uwe; Hermine, Olivier; Dybedal, Ingunn; et al. (Blood advances, 2022)
Advanced systemic mastocytosis (AdvSM) is a rare myeloid neoplasm, driven by the KIT D816V mutation in >90% of patients. Avapritinib, a potent, highly selective D816V-mutant KIT inhibitor, is approved for treatment of adults with AdvSM by the US Food and Drug Administration, regardless of prior therapy, and the European Medicines Agency for patients with prior systemic therapy, based on EXPLORER (#NCT02561988; clinicaltrials.gov) and PATHFINDER (#NCT03580655; clinicaltrials.gov) clinical studies. We present latest pooled efficacy and safety analyses from patients who received ≥1 systemic therapy prior to avapritinib in EXPLORER/PATHFINDER. Overall response rate in response-evaluable patients (n = 31) was 71% (95% confidence interval: 52% to 86%; 22/31), including 19% (6/31) with complete remission (CR)/CR with partial recovery of peripheral blood counts (CRh). Median time to response was 2.3 months, median time to CR/CRh was 7.4 months, and median duration of response (DOR) was not reached. Reductions ≥50% in bone marrow mast cell infiltration (89%), KIT D816V variant allele fraction (66%), serum tryptase (89%), and reductions ≥35% in spleen size (70%) occurred in most patients. Median OS was not reached (median follow-up 17.7 months). Avapritinib was effective in all AdvSM subtypes, regardless of number/type of prior therapies or poor prognostic somatic mutations. Treatment-related adverse events (TRAEs) were observed in 94% of patients, most commonly grade 1/2; 57% had TRAEs of at least grade 3; 81% remained on treatment at 6 months. Avapritinib in adults with AdvSM who received prior systemic therapy was generally well tolerated, with high response rates regardless of prior systemic therapy.